Numerical simulation of groundwater in an unconfined aquifer with a novel hybrid model (case study: Birjand Aquifer, Iran). Issue 1 (28th December 2021) - Mohtashami, Ali; Monfared, Seyed Arman Hashemi; Azizyan, Gholamreza; Akbarpour, Abolfazl
Abstract: In recent decades, due to the population growth and low precipitation, the overexploitation of ground water resources has become an important issue. To ensure a sustainable scheme for these resources, understanding the behavior of the aquifers is a key step. This study takes a numerical modeling approach to investigate the behavior of an unconfined aquifer in an arid area located in the east of Iran. A novel hybrid model is proposed that couples the numerical modeling to a data assimilation model to remove the uncertainty in the hydrodynamic parameters of the aquifer including the hydraulic conductivity coefficients and specific yields. The uncertainty that exists in these parameters results in unreliability of the head values acquired from the models. Meshless local Petrov-Galerkin (MLPG) is used as the numerical model, and particle filter (PF) is our data assimilation model. These models are implemented in the MATLAB software. We have calibrated and validated our PF-MLPG model by the observation head data from the piezometers. The RMSE in head values for our model and other commonly used numerical models in the literature including the finite difference method and MPLG are calculated as 0.166, 1.197 and 0.757 m, respectively. This fact shows the necessity of using this method in each aquifer. HIGHLIGHTS: The PF-MLPG method is compatible with different kinds of aquifers and different conditions, including confined, unconfined, transient, steady, irregular geometry and regular geometry. PF-MLPG simulates groundwater flow with satisfactory accuracy that helps decision makers to manage the aquifers properly. This new calibration–simulation model removes high uncertainty of model and input parameters such as hydraulic conductivity coefficient and specific yield.